Future predictions of global hotspots for temperature and precipitation extremes with CMIP6 model - Bayındır, Elif. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
This study used a climate change hotspot technique using population-weighted Standard Euclidean Distance (SED) measurements to assess climate change risks across regions. The analysis shows changes in the world’s climatology for the years 2026-2050 and 2076-2099 under the SSP2-4.5 and SSP3-7.0 scenarios. In the SSP2-4.5 scenario (2026-2050), equatorial regions like China, Japan, and Indonesia are hotspots that would experience increasing sea levels, extreme weather events, and heat waves because of a changing climate and population density. The Americas, Southern Africa, the Mediterranean, Western Europe, and Asia are considered to be risk zones. Concerns include droughts and unpredictable precipitation, which affect economies and food security. Ecosystems and communities must use customized adaptation strategies to meet these difficulties. Moderate adaption issues are anticipated under SSP2-4.5, necessitating focused measures. Distant future trends (2076-1999) align with near-future tendencies, which calls for further efforts. Similar indicator changes may cause a lack of differences between scenarios in the near future. This study enhances our understanding of hotspots and emphasizes the importance of thorough approaches. Innovations and a variety of situations improve climate resilience and adaptation. Future work should focus on improving assessment techniques, improving used data and models, and including socioeconomic issues for effective climate plans.
Keywords: Climate change mitigation.; Hazardous geographic environments -- Risk assessment.